An experimental study on coflow diffusion combustion in a pellet-packed bed with different bed lengths. Issue 8 (22nd August 2018) - Shi, Junrui; Liu, Yang; Liu, Yongqi; Mao, Mingming; Xia, Yongfang; Ma, Rui; Xu, Youning
Abstract : In experimental investigations on axial symmetry, over-ventilated CH4 /air diffusion combustion in a packed bed is executed to study the height, shape and stability of the flame. The combustor is a quartz tube packed with alumina pellets in which a cylindrical fuel stream is surrounded by a coflow air nozzle. The results show that the bed length and pellet diameter have a significant influence on the flame properties. In general, the flame above the pellet surface has axial symmetry, and its shape and colour are similar to those of a conventional diffusion flame when the bed length is smaller. The colour of the flame front varies with the bed length. The changed colour indicates an increased flame front temperature and that the combustion regime above the bed surface may change from non-premixed combustion to partially premixed combustion or even premixed combustion owing to the mix and dispersion effect in the packed bed. In addition, multiple flame behaviours, such as an inclined flame front, isolated reaction zone and oscillatory motion followed by a pulsating sound with a few hertz in a packed bed, are observed experimentally. The possible reasons for these phenomena are discussed.